IoT Applications in Fermented Tempe Production - Safrianti, Ery; Linna Oktaviana Sari; Fitri Wulandari; Feranita (International Journal of Electrical, Energy and Power System Engineering, 2022)
Tempe is made from fermented soybeans with the fungus Rhizopus Oligosporus. In the manufacture of tempe producers often experience failure. The main cause is the temperature and humidity of the room where the tempe production is not maintained. The absence of supporting devices for detecting temperature and humidity in the factory is an obstacle in the tempe fermentation process. Manufacturers can only estimate the temperature and humidity in the fermentation chamber. If the temperature is considered too hot, tempe producers will come to the factory and open the air vents so that the room temperature returns to normal. To increase tempe production and reduce the risk of production failure, it is necessary to design an automatic control and monitoring tool through the use of the Internet of Things (IoT). The tools used in this research are ESP8266, DHT22, Relay, Power Bank as a power source, fans, and lights. The results obtained from the test are that if the temperature and humidity are above or below the normal temperature (250C-320C), a notification will appear on the user's smartphone via the Blynk application. If the temperature is too hot, the fan will turn on automatically. If the temperature is too cold, the light will turn on. Monitoring data can also be viewed on the things peak website in graphic form.